Atlas of living cell cultures - Lindl, Toni.; Steubing, Rosemarie (Weinheim : Wiley-Blackwell, 2013)
The first atlas in many years giving researchers a good visual reference of the status of their cell lines. Given the increasing importance of well defined cellular models in particular in biomedical research this is a sorely needed resource for everyone performing cell culture.
3.2.11 Insect3.3 Human Primary Cells; 4 Cell Lines and Human Primary Cells; 4.1 Human Cell Lines; 4.2 Animal Cell Lines; 4.2.1 Rat; 4.2.2 Mouse; 4.2.3 Hamster; 4.2.4 Chicken; 4.2.5 Monkey; 4.2.6 Pig; 4.2.7 Opossum; 4.2.8 Potoroo; 4.2.9 Bovine; 4.2.10 Dog; 4.2.11 Insect; 4.3 Human Primary Cells; Appendix A: Materials and Suppliers; Appendix B: Suppliers of Cell Culture Materials; Further Reading; Index.
Includes bibliographical references (page 501) and index.
Text in English.
Print version record.
Keywords: Cell culture -- Atlases; Cell culture -- Atlases; Cell culture -- Technique; Cell; Cells -- Atlases; SCIENCE -- Life Sciences -- Cell Biology; Cell culture; Zellkultur; Electronic books; Atlases